Evaluating tourist sensory experience in Melaka world heritage site - Nur Hidayah Abd. Rahman, 1988- , author; Hairul Nizam Ismail, supervisor; Zainab Khalifah, supervisor; Fakulti Alam Bina (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Thesis (Doktor Falsafah) - Universiti Teknologi Malaysia, 2018